Rice-shaped Soy Protein Isolate–Alginate–Carrageenan Hydrogel: Physicochemical Properties and Digestion-associated Release Behavior - Tangmongkhonsuk, M; Chantieng, S; Balmori, V; Katelakha, K; Mahamud, N; Chusak, C; Hamid, Nazimah; Adisakwattana, S (Elsevier BV, 2026)
White rice is widely consumed as a staple food in many Asian populations, although it generally provides limited amounts of dietary fiber, micronutrients, and phytochemicals. Rice-shaped hydrogel systems may offer a potential structuring approach for incorporating plant-based protein ingredients into visually familiar food format. This study investigated the feasibility of forming rice-shaped soy protein isolate (SPI)–alginate–carrageenan hydrogel containing 4–8% SPI in alginate matrices (1.8%, w/v), with or without carrageenan (0–1%, w/v). Physicochemical, structural, and digestion-associated release properties were evaluated, and principal component analysis was used as a supportive tool to summarize formulation-dependent differences. Increasing SPI concentration influenced yield, water absorption, encapsulation efficiency, and textural properties. Carrageenan-containing formulations showed differences in morphology, hydration behavior, and SPI retention, suggesting possible changes in matrix organization. FTIR and XRD analyses indicated structural differences among formulations, potentially associated with interactions among SPI, alginate, carrageenan, and calcium ions. During simulated digestion, the ninhydrin assay indicated formulation-dependent release of amino-group-containing residues, with SPI8C1 showing the highest response, although this may partly reflect its higher initial SPI loading. Targeted LC–MS analysis detected selected isoflavone-associated compounds, including genistin, daidzin, and genistein, in SPI-containing hydrogel formulations. Overall, this study provides proof-of-concept information on formulation-dependent physicochemical, structural, and digestion-associated release properties of rice-shaped SPI–alginate–carrageenan hydrogels. Among the tested formulations, SPI8C1 exhibited the highest encapsulation efficiency and amino-group-containing residue release response, while carrageenan incorporation influenced hydration behavior, morphology, and matrix organization.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences; Bioengineering; Dietary Supplements; Nutrition; 3004 Crop and pasture production; 3006 Food sciences; Soy protein isolate; Encapsulation; Carrageenan; Digestion-associated release; Rice-shaped hydrogel